Grey matter abnormalities in Parkinson's disease: a voxel‐wise meta‐analysis. (23rd December 2019) - Xu, X.; Han, Q.; lin, J.; Wang, L.; Wu, F.; Shang, H.
Abstract : Background and purpose: The pathophysiology of Parkinson's disease (PD) remains unclear. Voxel‐based morphometry (VBM) detects local structural differences in brain tissue such as grey matter volume (GMV) between groups, which is helpful in understanding the pathophysiology of PD. Published VBM studies of GMV changes in PD have shown inconsistent results. Therefore, a voxel‐wise meta‐analysis of VBM studies was conducted to detect consistent GMV changes in PD. Methods: The published literature was searched comparing whole‐brain GMV between PD patients and healthy controls (HCs) using VBM. Coordinates were extracted for the clusters of significant GMV differences between PD patients and HCs. The meta‐analysis was performed by seed‐based d mapping software. Results: A total of 63 studies with 2867 PD patients and 1990 HCs were included. Significant GMV reductions in some brain regions were detected in PD patients, which were involved in the basal ganglia, theory of mind, vocal and visual networks. These findings remained largely unchanged in the jackknife sensitivity analysis, and no significant heterogeneity or publication bias was detected. Conclusions: Parkinson's disease patients have GMV reductions in a number of brain regions involved in specific networks. These findings provide morphological evidence for the pathophysiology of PD.